Evaluation of functional outcome by modified mayo wrist score in intra- articular distal end radius fracture managed by plate osteosynthesis - Verma, Ashish; Meena, Laxmi Narayan; Kumar, B. L. (International Journal of Research in Orthopaedics, 2022)
Background: Fractures of distal end of radius continue to pose a therapeutic challenge. Intra articular and extra articular malalignment can lead to various complications like post traumatic osteoarthrosis, decreased grip strength and endurance, as well as limited motion and carpal instability. Methods: A prospective study of forty patients with intra-articular distal end radial fractures treated under the department of orthopaedics, PIMS, Udaipur, were included in this study. All patients managed by plate osteosynthesis were followed up to 9 months. Results: When outcome according to modified Mayo wrist scoring system was assessed, only one patient (2.50%) scored with poor grade. 11 (27.50%) were graded as excellent, 19 (22.50%) as grade good, 9 (22.50%) as grade fair. 32 (80%) patients had union within 2-3 months and 06 (15%) patients had union in 3-4 months. There were 2 (5%) case of delayed union. Conclusions: Assessment of functional outcome by modified mayo wrist score in intra-articular distal end radius fracture managed by plate osteosynthesis gives an excellent scoring system to assess outcome of communited intrarticular distal radius fractures with reference to function of the hand and wrist of the individual. Also, it will help to predict the likely functional outcome in relation to fracture pattern of distal radius.